Thyroid disorders among patients with type II Diabetes Mellitus - Abdulla Hama Salih, Mariwan (Kurdistan Journal of Applied Research, 2019)
Recently hospitals are full of patient suffering from several chronic diseases. Two of these diseases are Diabetes Mellitus (DM) and Thyroid diseases. DM is a chronic disease characterized by irregular abnormal elevation of blood glucose level. It is classified in to several types depending on the situation; the major types are type I and type II. Thyroid disease is an endocrine disease which characterized by over production or decrease in production of thyroid hormones by thyroid glands. The main function of thyroid hormones is the regulation of body metabolism. Both of diseases are endocrine disease. These diseases currently the major hurdle among patient and become the great challenge in front of government capability to fight the problem. These data were collected between the last months of 2017 to the 15th of April 2018 from overall 300 patients. All the information has been collected from Diabetic and Endocrine Center, Shorsh Hospital and Medical DAIK Group in Sulaiman city. In total of 300 patients, Twenty five percent 25% of patients have both diabetes and thyroid disease. Fifty nine percent 59% of patients only have diabetes without any sign of thyroid problem, and finally only Sixteen percent 16% were have thyroid problem again without any evidence of having diabetes signs. This study showed that from the collection of (300) patients, seventy five (75) patients have both diabetes mellitus and thyroid diorders, these are more predominance in overage 40 years of mostly females, illiterate and housewife that mostly were insulaimani city.